Emissions of unintentional persistent organic pollutants from open burning of municipal solid waste from developing countries - Zhang, Tingting; Fiedler, Heidelore; Yu, Gang; Ochoa, Gustavo Solorzano; Carroll, William F.; Gullett, Brian K.; Marklund, Stellan; Touati, Abderrahmane (Chemosphere (Oxford), 2011)
► Sound methodology for measuring unintentional POPs was developed. ► Emission factors were derived to support UNEP Dioxin Toolkit. ► Waste composition did not affect emission factors. Open burning of waste is the most significant source of polychlorinated dibenzo-para-dioxins and dibenzofurans (PCDD/PCDF) in many national inventories prepared pursuant to the Stockholm Convention on Persistent Organic Pollutants. This is particularly true for developing countries. Emission factors for POPs such as PCDD/PCDF, dioxin-like polychlorinated biphenyls (dl-PCB) and penta- and hexachlorobenzenes (PeCBz/HCB) from open burning of municipal solid waste in China and Mexico are reported herein. Six different waste sources were studied varying from urban-industrial to semi-urban to rural. For PCDD/PCDF, the emission factors to air ranged from 3.0 to 650ngTEQkg−1waste and for dl-PCB from 0.092 to 54ngTEQkg−1waste. Emission factors for PeCBz (17–1200ngkg−1waste) and HCB (24–1300ngkg−1waste) spanned a wide but similar range. Within the datasets there is no indication of significant waste composition effect on emission factor with the exception of significantly higher Mexico rural samples.